THE IMPORTANCE OF TEACHING GLOBAL CITIZENSHIP AS A PROFESSIONAL SKILL TO PRE-SERVICE EFL TEACHERS (SCIENCE TIME JOURNAL, 2026)
This article explores the importance of teaching global citizenship as a professional skill to pre-service English as a Foreign Language (EFL) teachers. In the context of globalization and increasing intercultural communication, future EFL teachers are expected not only to possess linguistic competence but also to demonstrate awareness of global issues, cultural diversity, and social responsibility. The study analyzes theoretical frameworks related to global citizenship education and its integration into teacher training programs. It highlights the role of global competence in fostering critical thinking, intercultural communicative competence, and ethical responsibility among future educators. The paper also examines current practices and challenges in incorporating global citizenship into EFL teacher education, particularly within developing educational systems. The findings suggest that embedding global citizenship education into pre-service teacher training enhances professional readiness and prepares teachers to meet the demands of modern, globally interconnected classrooms.